Exposure of tungsten surface to high-flux of helium and argon ions - Bizyukov, I.O.; Girka, O.I.; Starovoitov, R.I.; Bizyukov, O.A.; Bobkov, V.V. (Вопросы атомной науки и техники, 2014)
Present work investigates the erosion yields of tungsten exposed to intense beams of He and Ar ions using weight-loss measurements. The ion beams were generated by FALCON ion source, typical particle fluxes were in the range of (0.4…1.0)×10²²m⁻²•s⁻¹ and the heat fluxes were 0.3…0.8 MW∙m⁻². Investigations show that the erosion yield for He ions is in line with simulations and experimental literature data on physical sputtering, while for Ar bombardment one has observed lower erosion yields. The morphology of the surface has also been studied with SEM. Исследуются коэффициенты эрозии вольфрама, измеренные с помощью метода потери веса. Образцы облучались интенсивными пучками ионов Не и Ar. Ионные пучки генерировались ионным источником FALCON, при этом плотность потока ионов составляла (0,4…1,0)×10²² м⁻²•с⁻¹, а тепловой поток на поверхность составлял 0,3…0,8 MВт∙м⁻². Исследования показали, что эрозия вольфрама под воздействием ионов Не соответствует результатам экспериментов и литературным данным по физическому распылению, в то время как при бомбардировке ионами Ar коэффициенты эрозии ниже. Досліджено коефіцієнти ерозії вольфраму, виміряні за допомогою методу втрати маси. Зразки опромінювались інтенсивними пучками іонів He та Ar. Іонні пучки з густиною потоку іонів (0,4…1,0)×10²² м⁻²•с⁻¹, та тепловими потоками 0,3…0,8 MВт∙м⁻² генерувались джерелом іонів FALCON. Дослідження показали, що ерозія вольфраму під дією іонів He узгоджується з результатами інших експериментів та літературними даними з фізичного розпилення. За умови бомбардування іонами Ar здобуті коефіцієнти ерозії виявились меншими за очікувані майже вдвічі. Морфологію опромінених поверхонь було досліджено за допомогою РЕМ.